Heat Tolerance Of Crossbred Jersey Cows In Semi-Arid Tropical Climate - Henry, A. Clement Ebenezer; Arunachalam, S.; Sivakumar , T.; Jagatheesan, P.N. Richard (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The study was conducted at Livestock Research Station, Kattupakkam, Tamilnadu Veterinary and Animal Sciences University with 55 randomly selected Jersey-Sindhi crossbred cattle, subjected to heat tolerance test expressed as index of tolerance to heat (ITH). The ITH of Jersey-Sindhi crossbred cattle was 8.51± 0.03 for lactating cow, 8.71 ± 0.05 for heifer and 8.60 ± 0.04 for dry cow in the scale 0 to 10, with 10 being the most heat tolerant. The heat tolerance index was not significant between seasons and also between different physiological status. The heat tolerating capacity of Jersey-Sindhi cross bred cattle in the present study is well enhanced and may be a choice for developing heat tolerant animals. The average daily milk yield of Jersey-Sindhi cross bred cattle were positively correlated with index of heat tolerance for winter (0.2522) and summer (0.6267) seasons. Hence, the index of tolerance to heat can be used as a tool for comparing animals in different environmental condition for their productive and reproductive performance.
Keywords: Jersey-Sindhi crossbred cattle; heat tolerance test; physiological status; rectal temperature